2014
DOI: 10.1186/s40359-014-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation among surgeons in Italy and Sweden – a cross-sectional study

Abstract: BackgroundSuicidal ideation is more prevalent among physicians, compared to the population in general, but little is known about the factors behind surgeons’ suicidal ideation. A surgeon’s work environment can be competitive and characterised by degrading experiences, which could contribute to burnout, depression and even thoughts of suicide. Being a surgeon has been reported to be predictor for not seeking help when psychological distressed. The aim of the present study was to investigate to what extent surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 33 publications
(62 reference statements)
2
48
0
4
Order By: Relevance
“…These 22 studies have been conducted in a variety of locations, including Germany,16 26 Norway,27 South Korea,28 29 the USA,30–32 France,33 China (Hong Kong Special Administrative Region),34 Australia,15 35 36 Canada37 and Sweden 38. There were two studies that reported data from more than one sample, one study reported data from Italy and Sweden39 and the second included data from Australia, China, Germany and South Korea 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 22 studies have been conducted in a variety of locations, including Germany,16 26 Norway,27 South Korea,28 29 the USA,30–32 France,33 China (Hong Kong Special Administrative Region),34 Australia,15 35 36 Canada37 and Sweden 38. There were two studies that reported data from more than one sample, one study reported data from Italy and Sweden39 and the second included data from Australia, China, Germany and South Korea 14…”
Section: Resultsmentioning
confidence: 99%
“…These suggest that analysis was potentially affected by an absence of studies finding non-significant associations between exposure to adverse psychosocial working conditions and suicidal ideation and/or behaviour. As a final sensitivity analysis, we removed Wall et al 38 from the analysis of working hours as this represented work–family conflict. Pooled results were largely unchanged (OR 1.69, 95% CI 0.85 to 3.34).…”
Section: Resultsmentioning
confidence: 99%
“…Social support can promote coping [10], diminish occupational stress [11,12] and reduce perceptions of depersonalization [13]. It can prevent psychiatric symptoms and common mental disorders [14,15] and has a protective function against possible suicidal intentions [16,17]. Low social support from co-workers is associated with emotional exhaustion [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Fridner et al [21] revealed that supportive environments when facing difficulties have protective effects on the risk of suicidal ideation among Swedish doctors. Other evidence from cross-sectional studies revealed that organizing a supportive meeting in the workplace had a favorable effect on reducing the risk of suicidal ideation [22,23]. Although suicidal ideation can be considered as the mentally unhealthy status of workers, organization-level support such as creating a supportive atmosphere, especially from their coworkers, may contribute to reduce workers' suicidal ideation regardless of their gender.…”
Section: Discussionmentioning
confidence: 96%
“…Although a further repeat study should be undertaken, differences between our results and Takada et al [30] might partly be attributed to the different measurement process of job demands; Takada et al [30] summed up each scores of job demands and reversed scores of job resources as an indicator of Bjob stressors.Ô ther proceeding studies revealed a significant association between interpersonal conflict and suicidal ideation. Wall et al [22] demonstrated a cross-sectional association between interpersonal conflicts such as Brecent degrading experiences^or Bharassment at work^and the risk of suicidal ideation among a total of 421 Italian and Swedish doctors. In Japan, Wada et al [31] conducted a cross-sectional study with 3862 doctors and found a significant association between interpersonal conflicts (unreasonable patient demands and complaints) reported in the previous 6 months and their suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%